La tutela procesal efectiva y su relación con la ley Nº30364 - Ley para prevenir, sancionar y erradicar la violencia contra las mujeres y los integrantes del grupo familiar - Sotomayor Berrocal, Javier Ángel (2024)
The present scientific research study seeks to identify the current interrelation between the rights that comprise Effective Procedural Protection within the scope of Procedural Law and Law No. 30364 – Law to prevent, punish and eradicate violence against women and members of the family group and its regulations. In this sense, although it is true that we are not going to develop the access to jurisdiction by the complainant in this type of process from the perspective of Effective Jurisdictional Protection, since this law allows the active legitimate party to be granted different mechanisms to access the Judiciary in order to determine whether or not the establishment of protection measures is pertinent, the present development will deal with other aspects such as the form of access to jurisdiction by the alleged aggressor, or within the scope of Effective Procedural Protection, the analysis of how these rights are developed linked to the right of defense, the right to prove, the right to contradiction, the right to substantial equality in the process, the right not to deviate from jurisdiction or be subjected to different procedures stipulated in the law, to obtain a resolution based on law, to access to appeal means, to the timely action of judicial resolutions, among others linked to it. In this sense, the investigation will allow us to see that from the analysis of the law and its practical application in the jurisdictional bodies, a possible violation of certain rights related to the Effective Procedural Protection can be identified, such as the jurisdictional malpractice of dispensing with hearings without further justification, the fact of not attaching to the resolution of the issuance of the protection measures the documents that gave rise to their issuance in the notification, allowing to observe an inadequate use of the chain of custody of the evidence that gives rise to the issuance of protection measures or in the appeal area the lack of setting a hearing of the case and the possibility of reporting orally to the higher body at the time of challenging the protection measures, especially to the aggressor party, since this resolution is considered an appeal without suspensive effect and without the quality of deferred, which according to the Civil Procedure Code does not oblige the appellant to be heard, as well as the impossibility of accessing the cassation appeal because its resolutions are not considered in one that It puts an end to the process. Consequently, while it is true that this law has achieved a very evident notoriety in our national reality, it is also true that in its development it has accumulated deficiencies that may affect due process. Therefore, in this way we seek to propose better practices from the jurisdictional sphere, as well as to propose that legislative modifications be made that grant minimum guarantees to the processing of this process and in this way guarantee the fundamental right to Effective Procedural Protection.